Wicked : the graphic novel. Part I - Maguire, Gregory; Hampton, Scott (William Morrow, an imprint of HarperCollins Publishers, 2025)
A graphic novelization of Gregory Maguire's "Wicked" in which Elphaba, born with emerald green skin, comes of age in the land of Oz, rooming with debutante Glinda at the university, and following a path in life that earns her the label of Wicked.